Halal Food Industry: Challenges and Opportunities in Europe - Nur Aini Fitriya Ardiani Aniqoh; Metta Renatie Hanastiana (Journal of Digital Marketing and Halal Industry, 2020)
The halal industry in Europe has experienced significant development, especially in the food sector. This study aims to analyze the challenges and opportunities of the halal food industry in Europe. The method uses a qualitative approach, with secondary data sources. The analysis technique uses a descriptive approach. The study results show that the development of the halal food industry in Europe was triggered by the increasing demand for halal certification and quality assurance, as well as the development of the tourism sector. This is a great opportunity for industry players to be able to meet the high demand for halal food. The challenge is how to improve quality and can meet halal standards to meet global demand.